Implementation of Child-Friendly Schools in the Success of Character Programs in the Independent Curriculum in Muhammadiyah 1 Krian Elementary Schools - Tirtoni, Feri; Amaliyah, Risma Inayatur; Pinasthi, Titah; Mubarokah, Risqina; Putri, Diva Nur Sabillah; Rosalinda, Melina (Procedia of Social Sciences and Humanities, 2024)
The implementation of the free curriculum at the muhammadiyah elementary school has been done with the purpose of strengthening character education through the pancasila student profile. The 1 krian elementary school for muhammadiyah has adopted the islamic and bilingual concept of a friendly school for children. The study USES a phenomenon's qualitative research approach. Data collection techniques through observation, documentation, and interviews. The data analysis technique using miles & huberman interactive model analysis. The implementation of free curriculum at the muhammadiyah primary school continues to strive to achieve the primary purpose of the curriculum implementation, which is to strengthen character education through the pancasila student profile. In application, however, it is clear that challenges cannot be ignored. Implementation of the child-friendly school concept in the Character Elementary School (SD) program in the Independent Curriculum is important to improve children's personality learning. Child-friendly schools create safe, peaceful and enjoyable areas, which pay attention to children's physical, psychological, social and intellectual needs. This can increase children's self-confidence, empathy, social skills, learning motivation, and active participation in school activities.